2021
DOI: 10.1073/pnas.2022649118
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium hijacks the high zinc response by binding and activating the HIZR-1 nuclear receptor

Abstract: Cadmium is an environmental pollutant and significant health hazard that is similar to the physiological metal zinc. In Caenorhabditis elegans, high zinc homeostasis is regulated by the high zinc activated nuclear receptor (HIZR-1) transcription factor. To define relationships between the responses to high zinc and cadmium, we analyzed transcription. Many genes were activated by both high zinc and cadmium, and hizr-1 was necessary for activation of a subset of these genes; in addition, many genes activated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…As expected, the damage is more extended at the lower concentration; the same evidence was obtained in the retina and kidney tubules [13,15]. Higher toxicity at a lower concentration can be explained considering that cadmium is a calcium and zinc mimetic and, by entering the cell at a low concentration, it may remain invisible to the detoxifying mechanisms [46,47]. Indeed, in villi of 25 µM Cd-treated animals, metallothioneins remain concentrated in the enterocyte's cytoplasm as in control villi, while MTs reduce significantly after 100 µM Cd exposure, presumably since it was used to detoxify the mucosa.…”
Section: Discussionsupporting
confidence: 65%
“…As expected, the damage is more extended at the lower concentration; the same evidence was obtained in the retina and kidney tubules [13,15]. Higher toxicity at a lower concentration can be explained considering that cadmium is a calcium and zinc mimetic and, by entering the cell at a low concentration, it may remain invisible to the detoxifying mechanisms [46,47]. Indeed, in villi of 25 µM Cd-treated animals, metallothioneins remain concentrated in the enterocyte's cytoplasm as in control villi, while MTs reduce significantly after 100 µM Cd exposure, presumably since it was used to detoxify the mucosa.…”
Section: Discussionsupporting
confidence: 65%
“…42,77 C. elegans has additional metal-responsive signaling mechanisms because numr-1/2 and many other genes can be strongly activated by cadmium independently of HIZR-1. 42 Repression of metallothionein genes by chaetocin and chetomin is also consistent with a distinct mechanism (Figures 3 and 7 and Figures S3 and S5). 77 Redox imbalance has been measured in cancer cells exposed to ETPs, 16,19,78 which is consistent with activation of HMOX1 and unfolded protein responses that we observed in HCT116 cells (Figure S6).…”
Section: ■ Discussionmentioning
confidence: 99%
“…We speculated that cadmium might play a physiological role at low levels somewhat, although it has not yet been discovered. Cadmium is chemically similar to zinc since they belong to group 12 of the periodic table and both elements are divalent d-block elements ( 44 ). Previous studies have shown that serum zinc levels are negatively correlated with diabetes and have positive glucose control outcomes ( 45 ).…”
Section: Discussionmentioning
confidence: 99%